2013
DOI: 10.1371/journal.pone.0070873
|View full text |Cite
|
Sign up to set email alerts
|

FoxP1 Stimulates Angiogenesis by Repressing the Inhibitory Guidance Protein Semaphorin 5B in Endothelial Cells

Abstract: Forkhead box (Fox) transcription factors are important regulators of cardiovascular development and several Fox-proteins have recently been shown to modulate embryonic and post-natal angiogenesis. However, the role of the FoxP subfamily, which is highly expressed in cardiovascular tissue, has not been investigated so far. Here, we show that the transcription factor FoxP1 is the highest expressed FoxP-protein in endothelial cells and that it is upregulated at the site of neovascularization during hindlimb ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…The dynamic effect of rs7632505 on CHD may be explained by the inhibitory effect of SEMA5B on angiogenesis which is related to aging process (Lähteenvuo and Rosenzweig, 2012 ) and is purported to be involved in atherosclerosis and other CVDs (Khurana et al, 2005 ; Deveza et al, 2012 ). SEMA5B is a member of the phylogenetically conserved class 5 semaphorins that all contain a characteristic Sema domain along with thrombospondin repeats (Adams et al, 1996 ) and is functionally important for angiogenesis (Iruela-Arispe et al, 1999 ; Chen et al, 2000 ; Grundmann et al, 2013 ). The moderate expression of SEMA5B is detected in multiple tissues including heart and brain (Nagase et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic effect of rs7632505 on CHD may be explained by the inhibitory effect of SEMA5B on angiogenesis which is related to aging process (Lähteenvuo and Rosenzweig, 2012 ) and is purported to be involved in atherosclerosis and other CVDs (Khurana et al, 2005 ; Deveza et al, 2012 ). SEMA5B is a member of the phylogenetically conserved class 5 semaphorins that all contain a characteristic Sema domain along with thrombospondin repeats (Adams et al, 1996 ) and is functionally important for angiogenesis (Iruela-Arispe et al, 1999 ; Chen et al, 2000 ; Grundmann et al, 2013 ). The moderate expression of SEMA5B is detected in multiple tissues including heart and brain (Nagase et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…This gene network may provide a clue to delineate the Foxp1 targets that modulate the morphogenesis of cortical neurons. In addition, a recent study found that FoxP1 stimulates angiogenesis by repressing semaphorin 5B (Sema5B) [ 59 ]. Since Sema5B is an inhibitory guidance cue for neuronal axons and is expressed in the cerebral cortex [ 60 , 61 ], this finding presents a possibility that Sema5B may be a target gene of Foxp1 for regulating the cortical development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, FOXP1 promotes angiogenesis by repressing the inhibitory guidance protein semaphorin 5B in endothelial cells. 31 Moreover, FOXP1 is upregulated in endothelial cells, smooth muscle cells, macrophages, and T cells of atherosclerotic plaque and is involved in the formation of stable plaques. 32 As another member of the FOXP family, FOXP2 plays an important role in the development of language.…”
Section: Introductionmentioning
confidence: 99%